Developing framework of Muslim consumer religiosity, brand preferences and purchase intention of halal food products in Malaysia / Johari Abdullah - Abdullah, Johari (2023)
Religiosity is an element of culture which is crucial in understanding individual preferences and intentions related to religion. It consists of religious belief, social and environmental responsiveness, norms and knowledge that influence human behaviour. Over the years, studies have relied on specific frameworks to explain related behaviour to understand the impact of religiosity. However, due to shortfalls in these frameworks, they may not be a complete basis to assess Muslim consumers, especially in their intentions to purchase Halal food products. Researchers assume that universal religiosity instruments are relevant across different religions and fields of study, but these instruments might not suit all frameworks. As a result, it may not be possible to adequately reflect nor explain religiosity factors for Muslim consumers. It also create the gap in understanding Muslim consumers from practitioners’ perspective in catering products that parallel their religiosity. This thesis aims to propose a new framework to fill these gaps. Muslim consumer religiosity is identified and its impact on purchase intention and brand preferences is assessed using an exploratory sequential mixed method research design.